TOE Framework Perspectives on Sustainability Practice Implementation: A Systematic Review - Sianturi, Parmonangan; Kesuma, Sambas Ade (International Journal of Demos (IJD), 2025)
Abstract This study aims to systematically review the factors influencing the implementation of sustainability practices through the lens of the Technology–Organization–Environment (TOE) framework. Using a Systematic Literature Review (SLR) approach guided by PRISMA procedures, 65 peer-reviewed articles were initially identified from the Scopus database, and 13 studies met the final inclusion criteria because they explicitly examined sustainability practices supported by technological, organizational, and environmental determinants. The included studies span various sustainability contexts, including green supply chain management, environmental management systems, green innovation, circular economy transitions, blockchain-enabled sustainable food and pharmaceutical supply chains, agricultural traceability, e-waste urban mining, and social sustainability in MSMEs. The reviewed studies employed diverse analytical techniques such as PLS-SEM, fsQCA, panel regression, Best–Worst Method, Grey-DEMATEL, and qualitative case studies, with sample sizes ranging from 8 experts to 495 organizational respondents. The findings of this review indicate that technological factors—such as digital readiness, perceived benefits, compatibility, and blockchain/AI capability—play a central role in driving sustainability implementation. Organizational determinants, including top management support, resource readiness, and internal sustainability commitment, function as essential enablers. Meanwhile, environmental forces such as regulatory pressure, institutional norms, market competition, and customer expectations strongly influence adoption decisions. Overall, this SLR demonstrates that sustainability implementation is not shaped by a single determinant but rather by configurational interactions among technology, organizational capabilities, and environmental pressures. These results offer theoretical insights for advancing sustainability adoption models and practical implications for organizations and policymakers striving to accelerate sustainability transformation. Keywords: Technology–Organization–Environment (TOE), sustainability, technology adoption, environmental performance, systematic literature review.